Methylene chloride poisoning in a cabinet worker. - Mahmud, M (1999)
More than a million workers are at risk for methylene chloride exposure. Aerosol sprays and paint stripping may also cause significant nonoccupational exposures. After methylene chloride inhalation, significant amounts of carbon monoxide are formed in vivo as a metabolic by-product. Poisoning predominantly affects the central nervous system and results from both carboxyhemoglobin formation and direct solvent-related narcosis. In this report, we describe a case of methylene chloride intoxication probably complicated by exogenous carbon monoxide exposure. The worker's presentation of intermittent headaches was consistent with both methylene chloride intoxication and carbon monoxide poisoning. The exposures and symptoms were corroborated by elevated carboxyhemoglobin saturations and a workplace inspection that documented significant exposures to both methylene chloride and carbon monoxide. When both carbon monoxide and methylene chloride are inhaled, additional carboxyhemoglobin formation is expected. Preventive efforts should include education, air monitoring, and periodic carboxyhemoglobin determinations. Methylene chloride should never be used in enclosed or poorly ventilated areas because of the well-documented dangers of loss of consciousness and death.